Libertad y justicia en las sociedades modernas - Salinas de Gortari, Carlos. (M.A. Porrúa Grupo Editorial, 1994)
"Contains some 50 essays dealing with ideological change, social welfare, individualism, liberty and justice, citizenship, governability, and political economy, presented at a conference funded by the Mexican Government. Authors include both leading Mexican and internationally distinguished scholars and intellectuals"--Handbook of Latin American Studies, v. 57.